Registered Nurses' and Nursing Students' Attitudes Towards Scientific Research: A Cross-Sectional Study - Nesibe Sumeyye Kütahyalioğlu; Gülşen Ulaş Karaahmetoğlu (Atatürk University, 2024)
Objective: The current study evaluated and compared nurses' and nursing students' attitudes towards nursing research and the factors affecting it. Methods: The study used a cross-sectional, descriptive survey design. Bedside nurses with at least one year of nursing experience and senior nursing students completed the Scale of Attitude towards Scientific Research, which is valid and reliable instrument. Results: There were no significant differences in the mean of overall score of Attitudes of Scientific Research across groups. However, significant differences were found in the mean scores of unwillingness to help researchers (P=0.002), positive attitudes towards research (P=0.002), and positive attitudes towards researchers (P=0.002) between nurses and nursing students. Additionally, the results showed significant differences in the mean of sub-scales based on nurses' education (P=0.04), responsibility (P=0.01), reading articles frequency (P=0.02), and nursing students' gender (P=0.03), and reading articles frequency (P=0.04). Overall, nursing students had significantly higher scores in positive attitudes of research (M=24.5, SD=4.6) and positive attitudes of researcher (M=23.6, SD=4.3) compare to nurses (M=22.5, SD=5.3; M=21.6, SD=5.1 respectively). Conclusion: Findings indicated that nursing students had significantly more positive attitudes to nursing research compare to registered nurses. Reading academic article is the only facilitator in each group that is associated with positive attitudes of scientific research. We recommend institutional support to encourage research activities and a revised nursing curriculum. Future studies should examine the relationships between attitudes towards research and the actual conducting of research.